Lobbying against environmental regulation vs. lobbying for loopholes - Andreas Polk; Armin Schmutzler (University of Zurich, Socioeconomic Institute, 2003)
We analyze the determinants of environmental policy when two firms engage in two types of lobbying against a restriction on allowed pollution: General lobbying increases the total amount of allowed pollution, which is beneficial for both firms. Private lobbying increases the individual pollution standard of the lobbying firm, but has a negative or zero effect on the allowed emissions of the competitor. We determine the lobbying equilibrium and discuss the resulting emission level. In many cases, a higher effectiveness of private lobbying is detrimental for firms and beneficial for environmental quality, as it induces firms to turn towards excessive amounts of relatively unproductive private lobbying.
Keywords: D72; D78; L51; 330; Environmental Regulation; Pollution Standards; Interest Groups; Lobbying; Policy Making; Umweltpolitik; Interessenpolitik; Interessenvertretung; Theorie; Politische Willensbildung